Peran Humas Perusahaan dalam Pelaksanaan Tanggung Jawab Sosial terhadap Masyarakat Desa Sekampil Kecamatan Pelepat Kabupaten Bungo Provinsi Jambi - Sri Wahyuni; Samsu; Sururudin (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2019)
This research was motivated by complaints from residents of Sekampil village who felt uncomfortable with the pollution of the river water they use for their daily life, which was allegedly due to the disposal of the company's factory waste into the river. On the other hand, the company wants to provide social responsibility or CSR grants. Public Relations is the company's bridge to communicate with the Sekampil community. The purpose of this study is to explain CSR and the role of public relations in this situation. The study found that the first implementation of corporate social responsibility at PT. Citra Sawit Harum has generally been implemented based on the applicable provisions, namely Law Number 40 of 2007 concerning Limited Liability Companies and Government Regulation Number 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies as the implementation regulations. However, in Sekampil there are still shortcomings in its implementation, namely the limited number of scholarships and community development. Although, overall, it has had a positive influence on the community around the company. In the future, the company must be more effective in carrying out social responsibility so that the community around the company does not feel disadvantaged by the existence of this limited liability company.